H3K4me2 ChIP-Seq reveals the epigenetic landscape during mushroom formation and novel developmental regulators of Schizophyllum commune - Peter Jan Vonk (Nature Portfolio, 2021)
Abstract Mushroom formation represents the most complex multicellular development in fungi. In the model mushroom Schizophyllum commune, comparative genomics and transcriptomics have previously resulted in a regulatory model of mushroom development. However, little is known about the role of epigenetic regulation. We used chromatin immunoprecipitation sequencing (ChIP-Seq) to determine the distribution of dimethylation of lysine 4 on histone H3 (H3K4me2), a mark for transcriptionally active genes, during monokaryotic and dikaryotic development. We identified a total of 6032 and 5889 sites during monokaryotic and dikaryotic development, respectively. The sites were strongly enriched near translation initiation sites of genes. Although the overall epigenetic landscape was similar between both conditions, we identified 837 sites of differential enrichment during monokaryotic or dikaryotic development, associated with 965 genes. Six transcription factor genes were enriched in H3K4me2 during dikaryotic development, indicating that these are epigenetically regulated during development. Deletion of two of these genes (fst1 and zfc7) resulted in arrested development of fruiting bodies, resulting in immature mushrooms. Together these results indicate that H3K4me2 ChIP-Seq is a powerful new tool to map the restructuring of the epigenetic landscape during mushroom development. Moreover, it can be used to identify novel developmental regulators.